Pengelolaan Peserta Didik dan Ekstrakurikuler - Ummah, Risa Rifdatul (Maliki Interdisciplinary Journal, 2025)
This study provides a comprehensive overview of student management within the rapidly evolving educational landscape shaped by technological advancements and shifting global demands. The discussion emphasizes the transition from traditional administrative approaches toward more human-centered, flexible models that prioritize the development of each learner’s potential. The implementation of the Merdeka Curriculum serves as a key driver of this transformation by promoting adaptive learning, character reinforcement, and enhanced digital literacy. This research also highlights the significance of three main dimensions—academic ability, character development, and skill acquisition—in shaping learners who are competent and aligned with 21st-century expectations. Furthermore, practical strategies such as digitalized management systems, teacher capacity building, innovative learning methods, and technology-based evaluation emerge as crucial components in optimizing student management. Overall, the study underscores that the success of educational transformation relies heavily on strong collaboration among teachers, schools, and stakeholders to build an inclusive, responsive, and future-oriented learning ecosystem.